2022
DOI: 10.3389/fneur.2021.744701
|View full text |Cite
|
Sign up to set email alerts
|

New Remote Cerebral Microbleeds on T2*-Weighted Echo Planar MRI After Intravenous Thrombolysis for Acute Ischemic Stroke

Abstract: BackgroundThe main and well-defined complication of intravenous administration of recombinant tissue plasminogen activator (tPA) in patients with acute ischemic stroke (AIS) is symptomatic intracranial hemorrhage (sICH). However, rtPA might also be connected with the formation of cerebral microbleeds (CMBs), located remotely from the ischemic lesions, that may remain clinically silent. This association might be important because the load of CMBs has been associated with cognitive impairment. We investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A previous study showed that intravenous thrombolysis with alteplase could improve the MMSE score at acute phase significantly than the control group [ 47 ]. However, a longitudinal study in alteplase treatment was inconsistent because the load of CMBs had been associated with cognitive impairment [ 48 ]. Thus, further studies are needed to explore the relationship between intravenous thrombolysis and PSCI.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that intravenous thrombolysis with alteplase could improve the MMSE score at acute phase significantly than the control group [ 47 ]. However, a longitudinal study in alteplase treatment was inconsistent because the load of CMBs had been associated with cognitive impairment [ 48 ]. Thus, further studies are needed to explore the relationship between intravenous thrombolysis and PSCI.…”
Section: Discussionmentioning
confidence: 99%